Asthma Induction During Development and Adult Lung Function, Behavior and Brain Gene Expression - Caulfield, Jasmine I.; Caruso, Michael J.; Bourne, Rebecca A.; Chirichella, Nicole R.; Klein, Laura C.; Craig, Timothy; Bonneau, Robert H.; August, Avery; Cavigelli, Sonia A. (Frontiers in Behavioral Neuroscience, 2018)
In developing youth, allergic asthma is the most common chronic condition, with 9-10% of youth affected. Asthma onset during childhood and adolescence is further associated with other health issues, particularly psychiatric conditions. To understand causal mechanisms by which developmental asthma may lead to altered behavior, brain and health trajectories, we developed a mouse model of developmental allergic asthma. In the current study, we tested for potential long-term effects of developmental asthma on adult lung function and behavior and brain gene expression associated with emotion and stress regulation. We manipulated airway inflammation and methacholine-induced bronchospasm (resulting in labored breathing) in young male and female BALB/cJ mice and measured adult outcomes three months after final asthma manipulations. Results indicated that allergen exposure, used to cause airway inflammation, and which ended on post-natal day 56, led to persistent lung airway inflammation, mucus buildup, and gene expression related to allergic asthma three months after final allergen exposure. In addition, at this same age, early allergen exposure led to altered brain gene expression related to stress regulation (prefrontal corticotropin releasing hormone receptor 1 and hippocampal glucocorticoid receptor) and serotonin function (brainstem serotonin transporter). On the other hand, labored breathing events during development led to altered anxiety-related behavior. Importantly, sex and pre-asthma fear-related behavior (ultrasonic vocalization rates) modulated these adult outcomes. Asthma that develops during childhood/adolescence may have long-term impacts on emotion and stress regulation mechanisms, and these influences may be moderated by sex and pre-asthma temperament.